Advancing global programmatic management of latent tuberculosis infection for at risk populations. Issue 5 (May 2016) - Getahun, Haileyesus; Matteelli, Alberto; Abubakar, Ibrahim; Hauer, Barbara; Pontali, Emanuele; Migliori, Giovanni Battista
In this issue of the European Respiratory Journal, Erkens et al. [1] present experience and results of long-term data (1993–2013) in the recording and reporting of latent tuberculosis (TB) infection (LTBI) management from the Netherlands. The authors report a high rate of initiation (77%) among the 37 729 eligible persons and a high rate of treatment completion (82%). Valid and complete data were available on almost all (96%) persons who started treatment, due to the use of a technically sound notification system supported by a legal framework and standardised indicators [1]. These findings are important additions to the renewed focus and call to address LTBI, which is considered as the reservoir for virtually all TB cases [2, 3]. Other renewed efforts include the establishment of a World Health Organization (WHO) global task force to raise the profile of programmatic management of LTBI, including monitoring and evaluation of implemented activities, as well as promoting research. UNITAID has also identified LTBI as one of its areas of intervention. Intensification of #LTBI treatment for child #TB contacts and people living with #HIV and other at risk populations http://ow.ly/ZfzAv